Nutritional Quality Assessment of Complementary Foods Produced from Fermented and Malted Quality Protein Maize Fortified with Soybean Flour - Abiose Sumbo H.; Ikujenlola Abiodun V.; Abioderin Florence I. (Polish Journal of Food and Nutrition Sciences)
Malnutrition of varying degrees has been associated with feeding infants with unwholesome and poor quality complementary foods. Therefore, the aim of this study was to produce complementary foods from quality protein maize (QPM) using the processes of malting and fermentation. The resulting flour was blended with processed soy bean flour at a ratio of 70:30 (maize: soybean). The nutritional qualities of the complementary foods were assessed biologically using animal feeding experiment to determine the growth rate, feed intake, protein quality parameters, haematological properties and rehabilitation potentials. The results showed that the protein efficiency ratio (PER) and food efficiency ratio of the malted QPM fortified with soybean were 2.44 and 0.24, respectively, which was the highest among the formulated diets and compared favourably with casein (2.5) and commercial diet (2.3). The QPM-based diets had a better biological value (<60%) and true dig stibility (<60%) than the products from normal maize. The packed cell volume of the samples ranged between 23.00 (basal) and 46.00% (soy fermented normal maize). The QPM-based diets enhanced the quick recovery of protein starved/depleted animals better than the NM-based diets. Moreover, the addition of soybean further boosted the ability of the diet to rehabilitate the animals. The best result was seen in the group of rats fed with soy-malted QPM. The use of QPM in complementary food formulation gave better results and could alleviate the problem of protein and energy malnutrition, thereby reducing the mortality rate among infants.